A novel polymer-free drug-eluting stent coated with everolimus using nitrogen-doped titanium dioxide film deposition in a porcine coronary restenosis model. (1st November 2016) - Sim, Doo Sun; Jeong, Myung Ho; Park, Dae Sung; Kim, Jung Ha; Lim, Kyung Seob; Bae, In Ho; Zhehao, Piao; Yang, Hae Young; Lee, Je Hoon; Hyun, Dae Young; Hong, Young Joon; Kim, Ju Han; et al.
Abstract: Background: Titanium dioxide (TiO2 ) films have superior biocompatibility and may be effective as drug-binding matrices for drug-eluting stents (DESs). We sought to evaluate efficacy of a polymer-free DES coated with everolimus using nitrogen-doped TiO2 film deposition in a porcine coronary restenosis model. Methods: Forty coronary arteries in 20 pigs were randomly allocated to group 1 (bare-metal stents (BMSs), 3.0 × 18 mm, n = 10), group 2 (BMSs with nitrogen-doped TiO2 film deposition, 3.0 × 18 mm, n = 10), group 3 [commercial everolimus-eluting stent, 3.0 × 18 mm, n = 10], and group 4 (polymer-free everolimus-eluting stent using nitrogen-doped TiO2 film deposition, 3.0 × 18 mm, n = 10). Stents were randomly implanted in the left anterior descending coronary artery and left circumflex artery with stent:artery ratio of 1.3. Four weeks later, pigs underwent follow-up coronary angiography and were sacrificed for histopathologic analysis. Results: Percent area stenosis was greater in group 1 compared to groups 3 and 4 (46.4 ± 13.8% vs. 30.2 ± 11.7% vs. 29.2 ± 8.9%, respectively, p = 0.005). Fibrin score was lower in groups 1 and 2, compared to groups 3 and 4: 0.87 ± 0.67 vs. 0.76 ± 0.61 vs. 2.27 ± 0.24 vs. 1.75 ± 0.31, respectively, p < 0.001). Injury score and inflammation score were not different. Comparison between DES showed a higher fibrin score in group 3 than group 4 (2.27 ± 0.24 vs. 1.75 ± 0.31, p = 0.023). Conclusions: In a porcine model of coronary restenosis, a novel polymer-free DES using nitrogen-doped TiO2 film deposition shows higher biocompatibility and compares favorably with a commercial DES. Highlights: TiO2 films may be effective as drug-binding matrices for drug-eluting stents (DESs). Polymer-free DES using nitrogen-doped TiO2 film shows higher biocompatibility. Further research is needed for longer-term effect of TiO2 polymer-free DESs.